1998
DOI: 10.1111/j.1945-5100.1998.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases and chemical composition of Shergotty mineral fractions, Chassigny, and Yamato 793605: The trapped argon‐40/argon‐36 ratio and ejection times of Martian meteorites

Abstract: Abstract-We report the elemental and isotopic composition of the noble gases as well as the chemical abundances in pyroxene, maskelynite/mesostasis glass, and bulk material of Shergotty and of bulk samples from Chassigny and Yamato 793605. The 4oK-4oAr isochron for the Shergotty minerals yields a gas retention age of 196 Ma, which is, within errors, in agreement with previously determined Rb-Sr internal isochron ages. Argon that was trapped at this time has a 40Ar136Ar ratio of 1100. For Chassigny and Y-793605… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
6
36
0
Order By: Relevance
“…The CRE age for the paired meteorite NWA 480, from analyses of both cosmogenic noble gases (Mathew et al, 2003) and 10 Be (Nishiizumi and Caffee, 2006), is similar to, if not identical to, CRE ages for ''enriched" basaltic shergottites Zagami, Shergotty, and Los Angeles (Eugster et al, 1997(Eugster et al, , 2002. Several analyses of Shergotty and Zagami in various laboratories gave a range in 36 Ar cos concentrations of 1.77-2.49 Â 10 À9 cm 3 /g for whole rock samples and 1.50-2.71 Â 10 À9 cm 3 /g for feldspar separates (Eugster et al, 1997;Terribilini et al, 1998;Park and Nagao, 2003;Park, 2005;Schwenzer et al, 2007). Variations in these 36 Ar cos values are to be expected because of variable sample composition and space shielding among individual samples.…”
Section: Ar-ar Isochron Agementioning
confidence: 90%
“…The CRE age for the paired meteorite NWA 480, from analyses of both cosmogenic noble gases (Mathew et al, 2003) and 10 Be (Nishiizumi and Caffee, 2006), is similar to, if not identical to, CRE ages for ''enriched" basaltic shergottites Zagami, Shergotty, and Los Angeles (Eugster et al, 1997(Eugster et al, , 2002. Several analyses of Shergotty and Zagami in various laboratories gave a range in 36 Ar cos concentrations of 1.77-2.49 Â 10 À9 cm 3 /g for whole rock samples and 1.50-2.71 Â 10 À9 cm 3 /g for feldspar separates (Eugster et al, 1997;Terribilini et al, 1998;Park and Nagao, 2003;Park, 2005;Schwenzer et al, 2007). Variations in these 36 Ar cos values are to be expected because of variable sample composition and space shielding among individual samples.…”
Section: Ar-ar Isochron Agementioning
confidence: 90%
“…On the other hand, Treiman et al (1994) found from the radionuclide activities of LEW88516 that most of its cosmic-ray exposure probably occurred as an individual meteoroid. Furthermore, the cosmogenic 22 Ne/ 21 Ne ratios are 1.227 ± 0.035 for LEW88516 (Eugster et al, 1997a) and 1.207 ± 0.020 for Y793605 (Terribilini et al, 1998), indicating irradiation as small bodies for the total duration of exposure. A complicated exposure history beginning with excavation of LEW88516 and Y793605, followed by ejection within 1-2 Myr, or reburial of these two rocks between their initial excavation and ejection, seems improbable.…”
Section: Crystallization and Ejection Agesmentioning
confidence: 98%
“…We begin our discussion with early Mars, working towards the present day. References: a1 Geiss and Hess (1958), recalculated to the K-decay constants by Steiger and Jäger (1977); a Eugster et al (1997a); b Bogard et al (1979); c Bogard and Garrison (1999); d Nyquist et al (1979a); e Jagoutz and Wänke (1986); f Shih et al (1982); g Chen and Wasserburg (1986); h Sano et al (2000); i Nyquist et al (1995); j Nyquist et al (2000); k Nyquist et al (1986); l Nyquist et al (2001); m Borg et al (1997); n Borg et al (2000); o , Jagoutz and Jotter (2000); p Miura et al (1995); q Jagoutz (1989); r Borg et al (2001b); s,t Borg et al (1998aBorg et al ( , 1998b; u Chen and Wasserburg (1993); v Misawa et al (1997); w Terribilini et al (1998).…”
Section: Radiometric Agesmentioning
confidence: 99%
“…In principle, it is also possible to obtain Ar-isochron ages, which date the rock formation, from Martian meteorites by plotting the ratio of trapped plus radiogenic 40 Ar to trapped 36 Ar ( 40 Ar tr + rad / 36 Ar tr ) versus K/ 36 Ar tr , the ratio of potassium to trapped 36 Ar (Terribilini et al 1998). However, it is unlikely that these agree with ages from undisturbed (by shock) isotopic systems.…”
Section: Argonmentioning
confidence: 99%
“…Ar is given in units of 10 −6 cc STP/g, Xe in 10 −12 cc STP/g. Stöffler et al (1986): average of all given analyses (min, max); b Terribilini et al (1998); c Smith and Hervig (1979); d Hale et al (1999); e Stolper and McSween (1979); f Bogard and Garrison (1999); g Shih et al 1982;h Treiman and Sutton (1991): range of all given analyses; i Steele and Smith (1982): range of all given analyses. Estimates of radiogenic 40 Ar are given in units of 10 −6 cc STP/g.…”
Section: Martian Interior Argonmentioning
confidence: 99%